Lejos de Chile, lejos de Francia: los exiliados chilenos en Diálogos de exiliados de Raúl Ruiz - Michèle Arrué (Les Cahiers ALHIM)
Dialogues of exiles is director Raul Ruiz's first feature film completed in France after fleeing from Chile to Europe following the coup d'état of 1973. In the form of micro narratives, the film depicts the everyday lives of Chilean exiles in Paris. Raul Ruiz portrays his characters in a way that makes them think, act and live as if they were still living in Chile. This shifted portrayal generates highly burlesque situations as the country they mentally continue to live in is Popular Unity Chile (1970-73). By way of resemantizing the discourses and practices of the micro community in exile and of inserting it in a different context, Raul Ruiz provides a powerful critical analysis of Popular Unity Chile.